The Effect of Using Google Sites as Learning Sources on Learning Outcomes of Students at SMK Negeri 4 Palangka Raya Academic Year 2021/2022 - Orbit Thomas; Simpun Simpun; Yulinda Yulinda (BIRCU, 2022)
Advanced data technology shares many positive benefits with the existence of the internet, not only helping to increase students' knowledge that is not available in school. With the Google site which has billions of websites, so that any information we are looking for is almost entirely available. Likewise with the subject matter, almost all of the subject matter is on this web, making it easier for students to do assignments so that it will have an impact on the acquisition of student learning outcomes. Raya for the academic year 2021/2022. This research is quantitative descriptive. The research sample is class XI Multimedia – 2 SMK Negeri 4 Palangka Raya students for the 2021/2022 academic year. Collecting data using questionnaires and documentation in the form of learning outcomes. While the data analysis technique used the Simple Regression test. The results showed that there was a positive and significant influence between the use of the Google site as a learning resource on student learning outcomes at SMK Negeri 4 Palangka Raya in the academic year 2021/20221 with a significance value of tcount of 0.010 < 0.05 with a large influence on the use of the Google site as a source learning on learning outcomes, which is equal to 20.8% and 79.2% is influenced by other factors not examined in this study.